Comparative Studies on the Antioxidant enzymes in Bone Marrow Precursor cells and mature Rat Polymorphonuclear Leukocytes (Global Journal of Medical Research, 2018)
Continuous blood cell production throughout the lifetime of an individual is ensured by the hematopoietic stem cells (HSCs), which are bone marrow cells that possess extensive self renewal capacity and ability to differentiate to all the blood cell lineages. The redox status of the bone marrow stroma is an important factor determining whether the HSCs would differentiate or remain quiescent. Lower levels of ROS (reactive oxygen species) are required to maintain HSC quiescence, whereas higher ROS levels drive the HSCs out of quiescence and reduces their self renewal capacity. The ROS levels in the bone marrow should therefore be regulated to maintain the self renewal capacity of HSCs. Endogenous antioxidants play an important role in regulation of the ROS levels. The present study was therefore undertaken to examine the changes in the cellular detoxifying defences against superoxide and H2O2 i.e. superoxide dismutase (SOD), catalase and glutathione peroxidase (GPx), in the precursor cells from the rat bone marrow and in the rat blood polymorphonuclear leukocytes. An increase in the Catalase and GPx activities in the precursor cells over the differentiated cells was seen. However, the SOD levels in the differentiated cells were greater than in the precursor cells. The levels of Nitric Oxide (NO)-an antioxidant and a regulator of superoxide generation-in the precursor cells were also found to be greater than those in the differentiated cells. The results of the present study thus indicate an up regulation of the endogenous antioxidants in hematopoietic precursor cells, which might be related to the maintenance of their self-renewal capacity.
Keywords: bone marrow precursor cells; polymorphonuclear leukocytes; antioxidants; nitric oxide